Hydrogels of cytoskeletal proteins : preparation, structure, and emergent functions /: preparation, structure, and emergent functions. (2016) - Osada, Yoshihito; Kawamura, Ryuzo, 1980-; Sano, Ken-Ichi
No abstract available